Superintense laser fields in circular array: effects of phase and pulse jitters - Ooi, Chong Heng Raymond; Tou, T.Y. (Springer, 2010)
Extremely intense laser field that makes nonlinear quantum vacuum can be generated by coherent superposition of multiple lasers in circular configuration that incorporates optical fibers synchronization scheme and piecewise mirrors in circular array operating below typical damage threshold. Coherent amplification and large laser beams can produce intensity reaching nonlinear quantum vacuum regime. The effects of phase jitter and envelope timing of the pulses due to imperfect synchronization are simulated and analyzed for both linear and circularly polarized pulses. We obtain simple analytical expressions that well describe the envelope jitter and phase jitter. Several practical aspects are discussed, including implications of scaling the laser dimension and pulse duration, with possibility for giant laser facility.